Applied geophysics for cover thickness mapping in the southern Thomson Orogen. Issue 7 (17th November 2018) - Roach, I. C.; Folkes, C. B.; Goodwin, J.; Holzschuh, J.; Jiang, W.; McPherson, A. A.; Meixner, A. J.
Abstract: Potentially mineralised Paleozoic basement rocks in the southern Thomson Orogen region of southern Queensland and northern New South Wales are covered by varying thicknesses of Mesozoic to Cenozoic sediments. To assess cover thickness and methods for estimating depth to basement, we collected new airborne electromagnetic (AEM), seismic refraction, seismic reflection and audio-frequency magnetotelluric data and combined these with new depth to magnetic basement models from airborne magnetic line data and ground gravity data along selected transects. The results of these investigations over two borehole sites, GSQ Eulo 1 and GSQ Eulo 2, show that cover thickness can be reliably assessed to within the confidence limits of the various techniques, but that caveats exist regarding the application of each of the disciplines. These techniques are part of a rapid-deployment explorers' toolbox of geophysical techniques that have been tested at two sites in Australia, the Stavely region of western Victoria, and now the southern Thomson Orogen in northern New South Wales and southern Queensland. The results shown here demonstrate that AEM and ground geophysics, and to a lesser extent depth to magnetic source modelling, can produce reliable results when applied to the common exploration problem of determining cover thickness. The results demonstrate that portable seismic systems, designed for geotechnical site investigations, are capable of imaging basement below 300 m of unlithified Eromanga Basin cover as refraction and reflection data. The results of all methods provide much information about the nature of the basement–cover interface and basement at borehole sites in the southern Thomson Orogen, in that the basement is usually weathered, the interface has paleotopography, and it can be recognised by its density, natural gamma, magnetic susceptibility and electrical conductivity contrasts.